2021
DOI: 10.1055/s-0041-1722942
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Morbidities and Complications of Neonatal İntensive Care Unit Patients with Respiratory Disorders at Different Gestational Ages

Abstract: Objective Respiratory distress presented within the first few days of life is life-threatening and common problem in the neonatal period. The aim of this study is to estimate (1) the incidence of respiratory diseases in newborns and related mortality; (2) the relationship between acute neonatal respiratory disorders rates and gestational age, birth weight, and gender; and (3) the incidence of complications associated with respiratory disturbances. Study Design Only inborn patients with gestational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…36 A study from the Netherlands reported that the PPHN rate in neonates with GA less than 30 weeks and/or extremely low birth weight infants was 11.5% (12/104), 37 while no PPHN cases were reported in a study on Turkish very preterm neonates. 38 The common causes of PPHN in very preterm neonates in this study were pneumonia and moderate or severe RDS. In a study from the Netherlands, multivariable logistic regression found that PPHN was associated with death, 37 which is similar to the findings in our study.…”
Section: Accepted Manuscriptmentioning
confidence: 64%
See 1 more Smart Citation
“…36 A study from the Netherlands reported that the PPHN rate in neonates with GA less than 30 weeks and/or extremely low birth weight infants was 11.5% (12/104), 37 while no PPHN cases were reported in a study on Turkish very preterm neonates. 38 The common causes of PPHN in very preterm neonates in this study were pneumonia and moderate or severe RDS. In a study from the Netherlands, multivariable logistic regression found that PPHN was associated with death, 37 which is similar to the findings in our study.…”
Section: Accepted Manuscriptmentioning
confidence: 64%
“…The first cranial ultrasound was performed within 3-5 days of birth for neonates with GA less than 26 weeks and 7-14 days of birth in neonates with GA of 26-32 weeks by a pediatric radiologist. The second cranial ultrasound was performed at GA 4-6 weeks of life or at [37][38][39][40][41][42] weeks in regards to postmenstrual age. Targeted neonatal echocardiography was performed by a neonatal fellow and/or pediatric cardiologist when a neonate was suspected to have patent ductus arteriosus (PDA) or PPHN.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Compared to past few years, survival rates of preterm infants have evidently raised with advances in perinatal and neonatal care (17). As a result, rates of very low birth weight (VLBW) and extremely low birth (ELBW) infants has increased.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory morbidities within the first few days of life are common and often life-threatening without prompt detection and treatment [ 1 ]. Respiratory failure requiring invasive mechanical ventilation decline with gestational age from approximately 95% for extremely preterm neonates (<28 weeks of gestation) to approximately 60% in very preterm neonates (28–32 weeks of gestation) and <1% for term neonates (≥37 weeks of gestation) [ 2 ]. Intrauterine inflammation is another key control variable of respiratory morbidity in neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably because of relatively more favorable outcomes related to respiratory morbidities in moderate-to-late preterm neonates than in their extremely and very preterm peers, respiratory morbidities other than RDS in this group of neonates have not been fully investigated, especially in relation to intrauterine inflammation. However, considering that the incidence of moderate-to-late preterm birth is approximately 5.5 times higher than that of extremely and very preterm birth [ 8 ] and that the prevalence of respiratory morbidities requiring invasive mechanical ventilation is approximately 30 times higher for moderate-to-late preterm neonates than for term infants [ 2 ], precise understanding of respiratory morbidities subsequent to intrauterine inflammation may improve the safety of this population. This study aimed to determine whether intrauterine inflammation – represented by the presence of funisitis, chorioamnionitis, and elevation of inflammatory biomarkers – is associated with respiratory morbidities requiring prolonged invasive mechanical ventilation in moderate-to-late preterm neonates.…”
Section: Introductionmentioning
confidence: 99%